2007
DOI: 10.1093/molbev/msm172
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal Virulence Is a Coincidental By-Product of Commensalism in B2 Phylogenetic Group Escherichia coli Strains

Abstract: The selective pressures leading to the evolution and maintenance of virulence in the case of facultative pathogens are quite unclear. For example, Escherichia coli, a commensal of the gut of warm-blooded animals and humans, can cause severe extraintestinal diseases, such as septicemia and meningitis, which represent evolutionary dead ends for the pathogen as they are associated to rapid host death and poor interhost transmission. Such infectious process has been linked to the presence of so-called "virulence g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
219
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(261 citation statements)
references
References 52 publications
28
219
1
3
Order By: Relevance
“…We found that isolates with the greatest content of VF genes were associated with the highest mortality. Interestingly, even a rectal isolate was capable of very high mortality, in agreement with the notion that virulence is a by-product of commensalism [24] (Fig. 3a).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found that isolates with the greatest content of VF genes were associated with the highest mortality. Interestingly, even a rectal isolate was capable of very high mortality, in agreement with the notion that virulence is a by-product of commensalism [24] (Fig. 3a).…”
Section: Discussionsupporting
confidence: 85%
“…The distribution pattern was similar among sites, although there was a trend towards a higher proportion of B2 in the respiratory tract than in the oropharyngeal and the rectal site (66, 51, and 49 %, respectively) sfa was screened in 18 pneumonia and 8 colonization isolates, and cnf1 was screened in 13 pneumonia and 6 colonization isolates UG ungrouped, NT non O1, O2a, O4, O6a, O7, O12, O15, O16, O18, O25a, O75, O157 a Determined by the triplex PCR method of Clermont et al [19] b According to Ref. [24] c Sequence type complex (STc) according to the Achtman multilocus sequence typing (MLST) scheme (http://mlst.ucc.ie) d According to Ref. [23] e The virulence genes were grouped in pathogenicity islands (PAIs) and plasmid as in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many strains belonging to this phylogenetic group cause extraintestinal infections, such as urinary tract infections and septicemia. Colibactin can thus be regarded as a VF of ExPEC, but little is known about its prevalence among isolates from defined clinical syndromes versus commensal strains or its associations with other VFs (13,16,25). In addition, certain commensal strains from healthy people also possess the pks island (13).…”
mentioning
confidence: 99%
“…Colibactin can thus be regarded as a VF of ExPEC, but little is known about its prevalence among isolates from defined clinical syndromes versus commensal strains or its associations with other VFs (13,16,25). In addition, certain commensal strains from healthy people also possess the pks island (13). Of note, one such commensal, the probiotic strain Nissle 1917, contains the pks island and produces a functional genotoxin (16).…”
mentioning
confidence: 99%